Characterization of EN-1078D, a poorly differentiated human endometrial carcinoma cell line: a novel tool to study endometrial invasion in vitro - Asselin Eric; Mes-Masson Anne-Marie; Provencher Diane; Van Themsche Celine; Dery Marie-Claude (Reproductive Biology and Endocrinology, 2007)
Abstract Background To date, tools to study metastasis in endometrial cancers are insufficiently developed. The aim of this study was to characterize the cell line EN-1078D, a new endometrial carcinoma cell line derived from a metastasis to the ovary. Methods and Results Cells were characterized using cytology, transmission electron microscopy, karyotyping and morphological appearance in culture. Molecular features were determined by RT-PCR, Western Blot, FISH and sequencing. MTT proliferation assays were performed to investigate the sensitivity of EN-1078D to anticancer agents such as cisplatin and doxorubicin. Also, subcutaneous and intravenous injections in nude mice were done to test the tumorigenic and metastatic properties of EN-1078D cells. Our results indicate that EN-1078D cells express both oestrogen receptors isoforms (ER alpha and ER beta) and also low levels of progesterone receptor B (PR-B). In addition, this cell line expresses high levels of MMP-2 and MMP-14 mRNA, low levels of TIMP-1 and TIMP-2 transcripts and no detectable levels of MMP-9 mRNA. Moreover, all nude mice developed tumors by subcutaneous injections and cell invasion was observed in vitro in response to TGF-beta 3. Her-2/neu was not overamplified but mutations in the C-2 domain of PTEN gene as well as codon 12 of the K-Ras gene were found. Finally, EN-1078D shows sensitivity to drugs commonly used in chemotherapy such as cisplatin and doxorubicin: IC50 of 2.8 μM of cisplatin after 72 hours of exposure and 0.54 μM of doxorubicin after 48 hours. Conclusion Taken together, these results suggest that EN-1078D will be an excellent tool to study the properties of metastatic endometrial cancer cells in vitro and their regulation by sex steroids.